Concur 2004 - concurrency theory proceedings - Gardner Philippa ed.; International Conference on Concurrency Theory, CONCUR 2004; International conference on concurrency theory, CONCUR 2004 London, UK 31 Aug - 3 Sep 2004 (Berlin Springer-Verlag, 2004)
Among the topics covered are concurrency related aspects of models of computation, semantic domains, process algebras, Petri nets, event structures, real-time systems, hybrid systems, decidability, model checking, verification techniques, refinement, term and graph rewriting, distributed programming, constraint logic programming, object-oriented programming, typing systems and algorithms, case studies, tools, and environments for programming and verification.
Keywords: Concurrency theory